BARIATRIC SURGERY IN A PUBLIC HOSPITAL IN MALAYSIA: THREE YEARS EXPERIENCE (2021- 2024) - Gerard, Adrian; Velayutham, Rama Moorthy; Supramaniam, Kumaresan; Rajandran, Aravinthan; Rahmahtullah, Ijaz bt Hallaj; Rahim, Anilah bt Abdul (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION Obesity in Malaysia has reached an alarming rate and various treatment modalities are available for patients depending on the severity of their obesity. Bariatric surgery has been proven to be part of the armamentarium to combat obesity; however, only a few public hospitals in Malaysia are capable of providing such a niche service. This study reports our experience over the past 3 years in a long-standing multidisciplinary bariatric clinic that was established in 2014 and based in a public hospital. METHODOLOGY Retrospective analysis of a prospectively maintained database of all patients undergoing bariatric surgery from January 2021 until April 2024 was performed. We analysed patient demographics, comorbidities and peri-operative complications. Prior to surgery, patients are thoroughly assessed, management of comorbidities is optimised, and the type of procedure and its expected outcomes are discussed in detail. Patients are required to be placed on an outpatient-based very low-calorie diet (VLCD) from 10 to 14 days prior to surgery. Peri-operative deep vein thrombosis prophylaxis is generally practiced unless contraindicated. RESULT A total of 125 patients underwent various bariatric procedures (75 sleeve gastrectomies, 40 Roux-en-Y gastric bypasses, 7 sleeve plus procedures, and 3 revisional procedures) with a mean age of 39.5 years and a mean BMI of 49.1 kg/m2 . The percentage of patients with diabetes, hypertension, and dyslipidaemia was 28.8%, 50.4% and 32% respectively. One patient was excluded as she required a conversion back to normal anatomy after gastric bypass. Throughout the study period, 3 major complications (Clavien-Dindo Grade III and above) were observed and 2 patients required readmission within one month due to dehydration. CONCLUSION This study shows that a multidisciplinary team with sufficient training and experience can provide bariatric surgery within a constrained public health system.